Exploring Education Gini on a Smaller Scale: How Education Inequality Differs among Districts - Nenny Hendajany; Deden Rizal Riyadi; Nor Aznin Abu Bakar (Jurnal Ekonomi dan Studi Pembangunan, 2022)
Decentralization creates a need to discuss education inequality on a smaller scale to formulate a better development policy. This study aims to give insights on how education inequality can vary across districts depending on the characteristics attributed to the said region. By calculating education Gini indices, we found that regencies and agricultural districts tend to experience worse education inequality than municipalities and non-agricultural districts. Adding to that, using panel data regressions, we also found that the data shows the opposite of education Kuznets curves, contradicting some of the previous studies. This study contributes to the literature by highlighting the importance of measuring education inequality in a smaller scale to improve the accuracy of development policies.